2013
DOI: 10.1007/s00418-013-1150-5
|View full text |Cite
|
Sign up to set email alerts
|

Segmental and restricted localization pattern of Fras1 in the developing meningeal basement membrane in mouse

Abstract: The Fras1/Frem family of extracellular matrix proteins consists of Fras1 and its structurally related proteins, Frem1 (Fras1-related extracellular matrix protein 1), Frem2 and Frem3. These are co-localized in embryonic epithelial basement membranes (BMs), where they contribute to epithelial-mesenchymal adhesion. Although Fras1 localization pattern in epithelial BMs has been well defined, it has not yet been comprehensively studied in the central nervous system. Here, we demonstrate the immunohistochemical prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Our findings indicate a possible involvement of Fras1 in the function of widespread brain areas, some of which lie deep in the brain parenchyma, remotely located from the meningeal BM, where Fras1 protein has been detected in the developing murine brain (Makrygiannis et al, 2013). Although the Fras1 gene is expressed in certain brain regions of juvenile mice, the corresponding protein could not be detected in neural tissue regardless of the different immunohistochemical methods applied.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Our findings indicate a possible involvement of Fras1 in the function of widespread brain areas, some of which lie deep in the brain parenchyma, remotely located from the meningeal BM, where Fras1 protein has been detected in the developing murine brain (Makrygiannis et al, 2013). Although the Fras1 gene is expressed in certain brain regions of juvenile mice, the corresponding protein could not be detected in neural tissue regardless of the different immunohistochemical methods applied.…”
Section: Discussionmentioning
confidence: 70%
“…The fluorescent protein signal was exclusively detected in embryos and neonates (P1) in the BM of choroid plexuses and in the meningeal BM (Figure 2f, g). It is noteworthy that Fras1 was not uniformly distributed throughout the embryonic meningeal BM but was rather spatially restricted, overlying certain brain regions, such as the hem, the septum and the medial prefrontal cortex, the preoptic area, the dorsal and the posterior–ventral diencephalon, and the dorsal and ventral midline of the midbrain and hindbrain (Makrygiannis et al., 2013). Although the mRNA in situ hybridization experiments revealed expression of Fras1 in various regions of the foetal and juvenile mouse brains, in immunohistochemical assays the specific for Fras1 antibodies identified the protein exclusively in the meningeal and choroidal BM and not within the nervous tissue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The family of Fras1/Frem extracellular matrix proteins comprises four structurally related members, Fras1, Frem1, Frem2, and Frem3, which are colocalized in embryonic epithelial basement membranes and contribute to epithelial-mesenchymal adhesion. Makrygiannis et al (2013) have studied the Fras1/Frem family in the developing mouse brain and revealed an exclusively meningeal basement membrane protein deposition. Furthermore, Fras1 displayed a segmental localization pattern since it was restricted to certain regions of the meningeal basement membrane.…”
Section: Connective Tissue and Extracellular Matrixmentioning
confidence: 99%